Efficiency of tocilizumab therapy for an exacerbation of systemic lupus erythematosus: A case report and a review of literature - S. K. Solovyev; A. A. Mesnyankina; D. E. Karateev; E. L. Luchikhina; Ya. A. Sigidin; E. A. Aseeva; A. V. Elonakov; E. L. Nasonov (Современная ревматология, 2017)
Interleukin-6 (IL-6) is one of the major proinflammatory cytokines, which, by interacting with hepatocytes, induces the synthesis of a broad spectrum of acute phase inflammatory proteins. IL-6 plays an important role in the development and progression of systemic lupus erythematosus (SLE), participates in the differentiation of CD4/CD8 regulatory T lymphocytes and in the production of autoantibodies by B lymphocytes, and increases the survival of plasmablasts. Tocilizumab (TCZ) is a humanized anti-IL-6 receptor antibody that neutralizes the pleiotropic effects of the cytokine. The use of this drug in SLE can have acceptable efficiency with the high inflammatory activity that is accompanied by fever, polyarthritis, polyserositis, skin lesions, and hemolytic anemia. The authors demonstrated the successful use of TCZ in a female patient with a documented diagnosis of SLE with a high activity (SLEDAI-2K-11). The use of the drug was justified by the prevalence of musculoarticular, constitutional (fever) disease, a high immunological activity (anti-DNA antibodies, 150 IU/ml; antinuclear factor, 1/1280 h; CRP, 88). This therapy could achieve complete relief of fever at day 2 after the first infusion of TCZ, a reduction, and subsequently complete relief of arthritis and normalization of laboratory blood parameters. TCZ has a satisfactory safety profile and may be considered as an alternative treatment for SLE when glucocorticoids, cytostatic agents, and rituximab are ineffective.